Qigong for Muscle Strength and Static Postural Control in Middle-Aged and Older Postmenopausal Women: A Randomized Controlled Trial - Carcelén-Fraile, María del Carmen; Aibar-Almazán, Agustín; Martínez-Amat, Antonio; Brandão-Loureiro, Vânia; Jiménez-García, José Daniel; Castellote-Caballero, Yolanda; Hita-Contreras, Fidel (Frontiers in Medicine, 2021)
In the present study, we aimed to determine the effects of a Qigong exercise program on the muscle strength and postural control in middle-aged and older postmenopausal women. This is a randomized clinical trial (https://clinicaltrials.gov/ct2/show/ NCT03989453) conducted on 125 women who were initially assigned to either an experimental group (n = 63) that performed a Qigong exercise program for 12 weeks or to a control group (n = 62) that did not receive any intervention. Muscle strength (dynamometer) and postural control (stabilometric platform) were evaluated before and immediately after an intervention period. The main findings of this study suggest that the women in the experimental group had improvements in muscle strength, mean velocity of the displacement of the center of pressure (CoP) with both eyes open and closed, and the surface sway area covered by the CoP, as well as the mediolateral and anteroposterior oscillations of the CoP, only with eyes open. The results of the present study determined that a 12-week Qigong exercise program has beneficial effects on muscle strength and postural control of middle-aged and older postmenopausal Spanish women.